PERBANDINGAN IMPLEMENTASI PEMBELAJARAN FIQIH SHALAT ANTARA PONDOK PESANTREN ANNIHAYAH RAWAMERTA DAN PONDOK PESANTREN ALBASHIIRAH KOTA BARU KARAWANG - Dita Distriani; Debibik Nabilatul Fauziah; Neng Ulya (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The diversity of Islamic organizations in Indonesia results in variations in the understanding and implementation of fiqh, including in the learning of fiqh on prayer in Islamic boarding schools. These differences constitute Islamic intellectual property that needs to be understood objectively to build tolerance for differences of opinion on fiqh issues. This research focuses on Annihayah Islamic Boarding School Rawamerta and Al-Bashiirah Islamic Boarding School Kota Baru Karawang. Although located in the same region, they have different manhaj backgrounds, making them interesting for comparative study. The purpose of this study is to analyze the implementation of fiqh learning on prayer, identify similarities and differences, and the factors that influence them. We will also evaluate the strengths and weaknesses of the learning in both Islamic boarding schools. This research uses a qualitative approach with a comparative case study method. Data were collected through observation, interviews, and documentation, then analyzed using data reduction, data presentation, and conclusion drawing methods using source and technique triangulation. The results of the study indicate that both Islamic boarding schools have similarities in learning objectives, primary sources of teachings based on the Qur'an and Hadith, and the application of learning methods that combine theory and practice to develop students' worship skills. However, there are differences in terms of learning planning, sources of fiqh references, methods of material delivery, implementation of worship practices, and evaluation systems, which are influenced by organizational backgrounds, scientific traditions, educator competencies, and policies of each Islamic boarding school. Annihayah Islamic Boarding School excels in habituating worship practices and the study of classical texts, while Al-Bashiirah Islamic Boarding School stands out in its systematic and evidence-based material delivery. These two learning models have complementary advantages and disadvantages and can be used as references for developing more effective, comprehensive, and adaptive prayer fiqh learning to meet the needs of students. Keywords: implementation of learning, fiqh of prayer, Islamic boarding schools, comparative studies, Islamic education.